2011
DOI: 10.13043/dys.68.7
|View full text |Cite
|
Sign up to set email alerts
|

Railroads in Peru: How Important Were They?

Abstract: This paper analyzes the evolution and main features of the railway system of Peru in the 19 th and early 20 th centuries. From mid-19 th century railroads were considered a promise for achieving progress. Several railroads were then built in Peru, especially in 1850-75 and in 1910-30. With the construction of railroads, Peruvians saved time in travelling and carrying freight. The faster service of railroads did not necessarily come at the cost of higher passenger fares and freight rates. Fares and rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For Brazilian railroads, Summerhill (1995) calculated a social saving of 22% of the GDP in 1913, and for Mexican railroads Coatsworth (1981) estimated a social saving of 24% of the GDP in 1910. Additionally, Zegarra (2011) concluded that that the Peruvian population saved time traveling and transporting freight at lower costs with the construction of railroads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Brazilian railroads, Summerhill (1995) calculated a social saving of 22% of the GDP in 1913, and for Mexican railroads Coatsworth (1981) estimated a social saving of 24% of the GDP in 1910. Additionally, Zegarra (2011) concluded that that the Peruvian population saved time traveling and transporting freight at lower costs with the construction of railroads.…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, Summerhill (1995) stated that coffee growers in Brazil benefited largely from the reduction in transportation costs due to railroad expansion. Similarly, Zegarra (2011) found that railroads in Peru had a significant impact on the growth of copper, sugar, and cotton exports, and in Chile, Guajardo (2007) points out that railways expanded markets and trade relations, linked the country to the international economy, and integrated regional and local markets into a national structure.…”
Section: Introductionmentioning
confidence: 99%